Penerapan Metode Design Thinking dalam Perancangan UI/UX Website Pintu Rumah - Roy Wenang Robbani; Ika Nur Fajri (Sekawan Institut, 2025)
Property rental is the activity of utilizing property by tenants for a certain period of time at an agreed-upon cost. The types of property rented include residential, commercial, and industrial, which are the choices of many people because of their flexibility. As technology evolves, property searches and transactions are now more accessible through digital platforms such as websites and mobile applications. This platform allows tenants or buyers to get faster and more precise in-formation according to their needs. However, many property rental platforms still face challenges in providing an optimal user experience, such as a complicated interface and a lack of direct in-teraction between tenants and property owners. This study aims to improve the user experience on property rental platforms by adding an appointment feature that allows direct communication between tenants and property owners. The method used in this study is Design Thinking, which consists of five stages: Empathy, Define, Ideate, Prototype, and Test. The developed prototype was tested using Maze, a real-time user testing platform. The test results show that this platform has a Maze Usability Score (MAUS) of 69.63%, which is classified as “Good”. Although in general the platform can be used well, there are areas that need improvement, such as the high level of click errors in the process of adding properties by the owner. The conclusion of this study is that alt-hough the platform functions effectively, there is still room for improvement in terms of clarity and ease of navigation.